PENGARUH OPERATING CASH FLOW (ARUS KAS OPERASI), DEBT TO EQUITY RATIO, CURRENT RATIO (CR), TOTAL ASSET TURN OVER (TATO) TERHADAP PROFITABILITAS PADA SEKTOR INDUSTRY BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2017 - Lilia, Wirda; Sitorus, Winda Sastra; Br. Tarigan, Pumpy Reydinda (Aksara Public, 2019)
This study aims to examine the effect of Operating Cash Flow, debt to equity ratio, current ratio (CR), total asset turn over (TATO) on profitability in consumer goods industry sector companies listed on the Indonesia stock exchange (BEI) . The samples of this study were 43 companies listed on the Indonesia stock exchange for the 2014-2017 period. Variable independent in this study were operating cash flow, debt to equity ratio, current ratio (CR), total asset turn over (TATO). While the dependent variable is profitability. The sampling technique is purposive sampling. Analysis of data with multiple linear regression, the results of this study indicate that the Operating Cash Flow variable partially has no effect and is not significant on profitability with a significant value of 0.515, Debt To Equity Ratio partially has no effect and is not significant to profitability with a significant value of 0.257, Current Partial ratio has no effect and is not significant with a significant value of 0.460, Total Asset Turn Over partially influential and not significant for profitability with a significant value of 0.438.